Superior Labral Anterior-Posterior (SLAP) Tears in the Military: A Clinical Review of Incidence, Diagnosis, and Treatment Compared With the Civilian Population. (November 2016) - Rossy, William; Sanchez, George; Sanchez, Anthony; Provencher, Matthew T.
Context: Given the notable physical demands placed on active members of the military, comprehension of recent trends in management and outcomes of superior labral anterior-posterior (SLAP) tears in this patient population is critical for successful treatment. Evidence Acquisition: Electronic databases, including PubMed, MEDLINE, and Embase, were reviewed for the years 1985 through 2016. Study Design: Database review. Level of Evidence: Level 5. Results: Active members of the military are at increased risk of sustaining shoulder injuries, particularly SLAP tears. Recent trends in management of SLAP lesions have shifted toward operative intervention. In the correct patient population, repairs of superior labrum tears demonstrate improved function and pain. Surgical repair of SLAP tears, especially in young and active military personnel, is supported. Conclusion: Military personnel are at greater risk of suffering a SLAP tear in comparison with their civilian counterparts. Surgical repair of these lesions is advocated in this subpopulation when the patient is younger than approximately 36 years of age, and if older, biceps tenodesis is likely superior.